Efektivitas Layanan Bimbingan Kelompok Teknik Role Playing Untuk Meningkatkan Regulasi Emosi Pada Siswa Di MTSN Lawe Sigala Gala - Anggraini, Ade Anggraini; Harahap, Ade Chita Putri (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2023)
According to Thompson, a person's inability to regulate emotions does not mean they are experiencing a psychological illness, but this inability is related to their emotional goals, so it can be said that they are unable to regulate their emotions. According to Nuraini (2018) emotional intelligence is a basic requirement for the success of a student who is in class in the learning process and is required to be able to speak in front of the class, because this ability is very useful for students to support the learning process and train students to express opinions in front of the teacher and other friends (Nuraini et al., 2018). The Role Playing technique is a type of service that is considered appropriate to contribute to students improving and developing a positive self-concept. Nuraini (2018) explained that through role playing techniques, students can improve their ability to respect themselves and the feelings of others, they can learn good behavior to handle difficult situations, and they can practice their ability to solve problems.